Perceived quality and value as mediator between student expectations, technical performance, and satisfaction on online interaction in a Chinese university - Wang, Xiaozhuan (2024)
The COVID-19 pandemic has significantly boosted the enrolment rate of online courses, with an increasing number of higher education institutions actively endorsing online learning through diverse digital platforms. Given the deteriorating natural environment and the influence of various unstable factors, online learning remains a vital teaching method for higher education institutions to navigate future unpredictable events. Despite the upward trend in online course enrolment both before and during the pandemic, the persistently low retention rate of such courses continues to pose a significant challenge, impeding the widespread promotion and development of online learning initiatives. This study proposes an International Student Satisfaction Index Model (ISSM) on the interaction of online international courses in Chinese universities, aiming to investigate the potential factors that affect international students’ online learning interaction. The model proposed in this study includes four antecedent variables, one target variable, and one outcome variable. This study is a quantitative research employing a survey research method. A pilot study was conducted on 50 international students from Zhejiang University of Science and Technology, China, to assess the reliability of the instrument. The Cronbach’s alpha values ranged from 0.705 to 0.969, indicating acceptable internal consistency. A stratified random sampling technique was employed to select a research sample of 320 international students enrolled in online courses. The collected empirical data were analysed using SPSS 26.0 and AMOS 21.0 software packages. The research results show that focusing on student satisfaction with online course interaction is conducive to improving the loyalty and retention rate of students (β=.147, p<.05). The key to improving international student satisfaction with online courses is to improve the overall perceived quality of international students’ interaction with online courses (β=.302, p<0.05). Students’ interaction expectations before participating in online courses (β=.185, p<.05), the perceived value after participating in online courses (β=.2, p<.05), and online technology performance (β=.182, p<.05) are also factors that cannot be ignored when improving student satisfaction. The mediation analysis results validate the mediating roles of perceived quality and perceived value. In addition, students’ gender and students’ major do not affect student satisfaction with online courses. To a certain extent, this study fills in the gaps in the research field of the online learning student satisfaction index model and provides a new research perspective. In addition to advancing the development of related literature in this field, this study also expands the empirical research scope of the online course student satisfaction index model. The results of this study are conducive to promoting the reform of online international courses in the field of higher education in China and improving the online retention rate of international students.